Relationship between the Quality of Informed Consent at Surgical Procedure in Terms of Ethics and Medicolegal with Satisfaction of Patient Health Service in dr. Zainoel Abidin Hospital - Taufik Suryadi Ismail; Putra Safana; Dedy Syahrizal (International Journal of Integrated Health Sciences, 2020)
Objective: To determine the relationship between the quality of informed consent in terms of ethics and medicolegal with patient health service satisfaction at the dr. Zainoel Abidin Hospital (ZAH) Banda Aceh.Method: This study is an observational analytic with a cross-sectional method. Subject selection through a total sampling method. This study involved patients who were treated at dr. Zainoel Abidin Hospital (ZAH) Banda Aceh and a total of patients were 100 (52 men and 48 women) who met the inclusion criteria carried out on 16 December 2019 to 31 December 2019.Results: As many as 90% of respondents rated informed consent made at ZAH as good quality and 85% expressed the satisfaction with health services at ZAH. An ethical and medicolegal review of informed consent emphasizes the basic principles of bioethics. As many as 84% of respondents stated that their autonomy rights had been fulfilled, 92.50% thought that the doctor had done beneficence, nonmaleficence, and justice well in the process of informed consent and 92.33% of respondents rated the three elements of informed consent as being well implemented. Based on the results of the chi-square statistical test showed a significant relationship between the quality of informed consent in terms of ethics and medicolegal with patient health service satisfaction under the value of p = 0.001 (p≤0.05).Conclusion: Good quality of informed consent in terms of ethics and medicolegal has an important role in increasing patient satisfaction with health services at the dr. Zainoel Abidin Hospital of Banda Aceh.